Causality of Fraud Detection - Muslim Muslim, Darwis Lannai (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
The purpose of this study is to examine the effect of experience, independence, implementation ethic and workload to fraud detection. Collecting data in this study using a questionnaire instrument with a sample of 52 auditors KAP in Makassar city using the saturated sampling technique. The analytical method used is the Partial Least Square (PLS) approach. The results of this study indicate that experience and implementation ethic had a positive and significant effect on fraud detection. While independence and workload had a positive but not significant influence on fraud detection.